2020
DOI: 10.1002/cche.10328
|View full text |Cite
|
Sign up to set email alerts
|

Effects of barley β‐glucan with various molecular weights partially hydrolyzed by endogenous β‐glucanase on glucose tolerance and lipid metabolism in mice

Abstract: Background and objectives In this study, we investigated whether the intake of a high‐fat diet containing barley β‐glucan partially hydrolyzed by endogenous β‐glucanase (PHEB) for 2 or 8 hr affects glucose metabolism, lipid metabolism, and intestinal microbiota compared with untreated barley (BF) and a control diet in mice. Findings A significant increase in cecum weight was observed in all barley groups compared with the control group. Liver lipid accumulation was significantly decreased in all barley groups.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Therefore, the correlation coefficient observed in this study suggests that increased levels of lactic acid-producing bacteria brought about by an intake of HGB flour may have enhanced the concentration of sIgA through the intestinal immune response. Our previous investigations have shown that the ingestion of HGB flour increases the levels of lactic acid-producing bacteria [ 49 ], but this is the first such study to report an effect on immune function. Further research is needed to clarify the species of lactic acid bacteria increased by the intake of HGB flour and to investigate their functions.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, the correlation coefficient observed in this study suggests that increased levels of lactic acid-producing bacteria brought about by an intake of HGB flour may have enhanced the concentration of sIgA through the intestinal immune response. Our previous investigations have shown that the ingestion of HGB flour increases the levels of lactic acid-producing bacteria [ 49 ], but this is the first such study to report an effect on immune function. Further research is needed to clarify the species of lactic acid bacteria increased by the intake of HGB flour and to investigate their functions.…”
Section: Discussionmentioning
confidence: 92%
“…It has been generally recognized that the preventive effect of barley intake on postprandial blood glucose rise is triggered by delayed gastric emptying time due to the viscous properties of barley β-glucan and the suppression of digestion and absorption of starch in barley [ 32 , 33 ]. However, our previous report showed that improvement of glucose tolerance became more pronounced when HGB with partially hydrolyzed β-glucan was supplemented into the test diet [ 34 ]. It is possible that a prebiotic effect, such as intestinal fermentation, contributed more to the improved glucose tolerance than the physicochemical effect, such as increased viscosity.…”
Section: Discussionmentioning
confidence: 99%
“…Sample sizes were determined from our previous study [ 18 ]. Twenty-four mice (8 mice per group) were used.…”
Section: Methodsmentioning
confidence: 99%
“…This discrepancy was explained by the experimental condition, such as excessive doses of β-glucan (6.8–8.4%). Our previous study showed that partially hydrolyzed barley β-glucan (50 and 110 kDa, 2.5% β-glucan in the diet) demonstrated the physiological functions similar to intact barley β-glucan which improved glucose and lipid metabolism [ 18 ].…”
Section: Introductionmentioning
confidence: 99%